Leadership as a Strategic Management Instrument: A Systematic Review and Conceptual Framework - I Dewa Gede Sayang Adi Yadnya; Heny Hendrayati; Eeng Ahman; Yana Setiawan; Askolani Askolani; Rasto Rasto (Fundamental and Applied Management Journal, 2026)
Organizations need leadership that connects long-term direction with operational execution under conditions of rapid technological, social, and environmental change. This review synthesizes recent evidence on leadership functions across strategy formulation, implementation, monitoring, and evaluation and develops a framework for later empirical testing. Scopus was searched through 23 July 2026 using leadership and strategic-management terms. Eligible records were peer-reviewed, open-access, English-language journal articles published from 2022 to the search date, available in full text, and reporting an extractable relationship between leadership and at least one strategic-management stage. From 180 records, 27 studies met the criteria. Twenty-two empirical studies were appraised with the Mixed Methods Appraisal Tool, five non-empirical studies were identified separately, and all studies were synthesized thematically. The corpus comprised two studies from 2022, two from 2023, ten from 2024, ten from 2025, and three from 2026. Fourteen empirical studies met all applicable MMAT criteria, seven had one reporting concern, and one had two concerns. The synthesis identified leadership functions related to innovation, sustainability governance, and digital transformation and mapped these functions across strategic-management stages. The mediating role of strategic-management processes and the conditioning roles of collaborative culture and hierarchical rigidity are author-developed propositions rather than review findings. Leadership can be treated as an organizational mechanism that aligns vision, resources, and action, but the proposed relationships require empirical validation.